Problematika Sakralitas dalam Media Hiburan: Telaah Fikih terhadap Game “Ghaib”: The Problematics of Sacredness in Entertainment Media: A Fiqh Analysis of the Game “Ghaib” - Salman Al Farisi (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
The presence of holy Islamic material in popular media is a grave matter morally and legally—particularly when Qur'anic passages are used in entertainment media. "Ghaib," an Indonesian horror video game, employs Qur'anic recitals as holy weapons against ghosts, provoking worldwide fame and controversy. This study deviates from the topic of disrespect for the Qur'an in contemporary digital culture, especially when it is set within contexts that go against its sacred nature. Therefore, this research aims to explore the relevance of the rules of fiqh adab in the Quran to the case of the game “Ghaib” and its implications. Employing qualitative descriptive-analytical methods, this study draws on classical fiqh literature, contemporary scholarly research, and digital ethnography. Findings indicate that the game is failing to uphold adab (etiquette) towards the Qur'an and being primarily entertainment-oriented. In accordance with fiqh principle—namely the rule of thumb that when halal and haram are mixed, the haram dominates—the study concludes that such use of the Qur'an is not allowed (haram), and could constitute kufr if disrespectful. This research highlights the importance of affirming Qur'anic sacredness in digital culture and provides ethical standards for Muslim gamers and game creators. In addition, this research contributes to preventing the stagnation of ancient ethical practices by testing their implementation in the present day.